Long-term effects of siponimod on cardiovascular and autonomic nervous system in secondary progressive multiple sclerosis - Constantinescu, Victor; Haase, Rocco; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Pharmacology, 2024)
Siponimod, a second-generation, selective sphingosine 1-phosphate receptor (S1PR) 1 and 5 modulator, represents an important therapeutic choice for active secondary progressive multiple sclerosis (SPMS). Besides the beneficial immunomodulatory effects, siponimod impacts cardiovascular function through S1PR1 modulation. Short-term vagomimetic effects on cardiac activity have proved to be mitigated by dose titration. However, long-term consequences are less known.Objectives: This study aimed to investigate the long-term impact of siponimod on cardiac autonomic modulation in people with SPMS (pwSPMS).Methods: Heart rate variability (HRV) and vascular hemodynamic parameters were evaluated using Multiple Trigonometric Regressive Spectral analysis in 47 pwSPMS before siponimod therapy and after one, three, six and twelve months of treatment. Autonomic activation tests (tilt test for the sympathetic and deep breathing test for the parasympathetic cardiac modulation) were performed at each examination.Results: pwSPMS preserved regular cardiovascular modulation responses during the autonomic tests reflected in the variation of several HRV parameters, such as RMSSD, pNN50, total power of HRV, high-frequency and low-frequency bands of the spectral domain or hemodynamic vascular parameters (Cwk, Zao, TPR, MAP) and baroreflex sensitivity (BRS). In the long-term follow-up, RMSSD, pNN50, total power, BRS and CwK presented a significant decrease, underlining a reduction of the parasympathetic and a shift towards sympathetic predominance in cardiac autonomic modulation that tends to stabilise after one year of treatment.Due to dose titration, the short-term effects of siponimod on cardiac autonomic modulation are mitigated. The long-term impact on cardiac autonomic modulation is similar to fingolimod. The autonomic activation tests showed normal cardiovascular responses during oneyear follow-up in pwSPMS, confirming the safety profile of siponimod. Further research on autonomic function could reveal whether the observed sympathetic activation is a compensatory response to S1P signaling intervention or a feature of the disease, while also shedding light on the role of S1PR modulation in MS.